Community Empowerment of Perlis Village, West Brandan, Langkat through Mangrove Restoration and Clean Water Supply Activities : Pemberdayaan Masyarakat Desa Perlis, Brandan Barat, Langkat melalui Kegiatan Pemulihan Mangrove dan Penyediaan Air Bersih - Mohammad Basyuni; Alfian Mubaraq; Andi Aznan Aznawi; Astrid Fauzia Dewinta; Irvan Irvan; Julia Syahriani Hasibuan; Itchika Sivaipram; Venus E Leopardas; OK Hasnanda Syahputra; Netti Herlina Siregar; Oke Rina Ramayani; Yunilda Andriyani; Nurdin Sulistiyono (Institut Riset dan Publikasi Indonesia, 2025)
The mangrove forests of Perlis Village, West Brandan, Langkat have suffered degradation due to illegal logging, agricultural conversion, and seawater intrusion, causing severe ecological and socioeconomic challenges. This study aimed to restore the mangrove ecosystem and improve access to clean water, addressing the community's urgent needs while supporting sustainable development goals. The project significantly enhanced the livelihoods of local fishermen, provided reliable clean water access, and fostered environmental stewardship. By combining ecological restoration with infrastructure development, it offered a replicable model for addressing environmental and social challenges in coastal communities. A participatory approach was employed, involving community engagement in planning, capacity-building workshops, and ecological restoration activities. Mangrove saplings were planted, and a clean water supply system was established through collaborative efforts between community members and external stakeholders. The project successfully restored 5 hectares of mangroves, increasing biodiversity and reducing coastal erosion. The survival rate of planted saplings was 85%. The clean water system expanded access from 40% to 85% of households, significantly reducing waterborne diseases and the time spent fetching water, especially for women and children. The initiative demonstrated that integrated community-driven interventions can address complex environmental and social issues effectively. The outcomes align with the study's objectives, providing valuable insights into sustainable development practices and the empowerment of coastal communities.